(3GdfXQjI GdYGeI ddGeJfGY ai GdbGfhf GdLfGFi (B/ s - (3eMeO GMeO eUWai GjhHs; (3eGehf SdGeI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2003)
(3Ef SHHjI GdGeJfGY dG JNJda Yf SHHjI GdaYd GdEjLGHj, hCfg jLH Ydi GdeTQ Cf jJONd hHfU UQjM dG jbHd GdJChjd jbQ ajg HUdGMjI GdSdhc GdSdHj Ch GdGeJf dcj JJMbb Hg GdfJjLI GdELQGejI(B. (3hdf jJCJi Pdc EdG EPG GYJQa GdeTQY UQGMI HYdG GdSHHjI Hjf GdGeJfGY hGdfJjLI GdELQGejI, hHeSFhdjI GdeeJfY Yf Jdc GdfJjLI ceG dh c` bO CMOKgG HaYdg GdEjLGHj, hJHYG deG EPG cGf bO JhGaQ dOjg GdbUO GdLfGFj Ch GdNWC Y GdYeOj heHQQfG aj gPG GdWdH Cf GdedGMXGJ aj Xd ZjGH gPG GdfU GdPj jYJQ HYdGbI GdSHHjI Hjf GdGeJfGY hGdfJjLI GdELQGejI Cf GdcKjQ ef GdLQGFe GdJj JQJcH HSd SdHj Ch GeJfGY (B- (3NUhUG ef bHd GdCTNGU GdeYfhjI (B- (3dG jDGNP eQJcHgG Yc GeJfGYg QZe eG bO jDOj Edjg Pdc GdGeJfGY ef fJGFL NWjQI HOYhi YOe hLhO f bGfhfj jKHJ GdUdI Hjf gPG GdGeJfGY hJdc GdfJjLI hjLQe HGdJGdj GdSdhc GdSdHj(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2003s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B452-501s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3LQjeI GdGeJfGYs; (3GQcGf GdGeJfGYs; (3GdGeJfGY GdeJHhY HLQjeIs; (3GdGeJfGY GdeLQO s; (3GdOaGY GdTQYj hGdGeJfGYs; (3fXQjI JYOO GdLQGFes; (3LQjeI GeJfGY GdbGVj Yf GdaUd aj GdOYhjs; (3GdGeJfGY Yf OaY GdfabIs; (3GdGeJfGY Yf JSdje Wad eMche HMVGfJg Gh MaXg Gh NWags; (3LQGFe GdGeJfGY GdeJYdbI HGdHjFIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs